A back side configured pointed dipole plasmonic optical antenna array enhanced quantum dot infrared photodetector. (20th November 2017) - Lu, Xuejun; Mojaverian, Neda; Li, Lin; Gu, Guiru; Zhang, Yingjie; Kemsri, Thitikorn
Abstract: In this paper, we report a back side configured pointed dipole optical antenna array enhanced quantum dot infrared photodetector (QDIP). In this configuration, the light illumination is from the substrate side (i.e. back side illumination), goes through the QDIP and then reaches the optical antenna array. The near-field electric fields (E-fields) are simulated for both top and back side illuminations. The back side configured pointed dipole antenna array gives stronger E-fields than the top side configuration. The physical mechanism for the difference is analyzed. A longwave infrared QDIP with the back side configured pointed dipole optical antenna array was fabricated and tested. The measurements agree well with the simulation. Compared with the top side configured optical antenna array, the back side configured optical antenna array allows easier fabrication of large format (e.g. 640 × 512 or 1024 × 1024) focal plane arrays and provides higher plasmonic enhancement.